Sequential evaluation for bone union of transferred fibula flaps in reconstructed mandibles: panoramic X-ray versus computed tomography. Issue 8 (August 2015) - Akashi, M.; Hashikawa, K.; Kakei, Y.; Sakakibara, A.; Hasegawa, T.; Minamikawa, T.; Komori, T.
Abstract The purpose of this study was to sequentially evaluate bone union of fibular grafts in mandibular reconstruction. Patients who underwent routine follow-up computed tomography (CT) and panoramic X-ray imaging during a period of ≥2 years were enrolled. On panoramic X-ray images, bone union was scored as 0 (absent callus formation) or 1 (complete callus formation). On CT images, a scale of 0 to 2 was used (0, absent callus formation; 1, complete callus formation only on the labial side; 2, complete callus formation on both the labial and lingual side). A total of 56 bone junctions were evaluated in 20 patients. Five of 56 junctions (9%) in four of 20 patients (20%) showed radiological non-union (panoramic X-ray score = 0, CT score = 0 or 1) at 2 years after surgery. All bone junctions with radiological non-union were located at the mandibular angle. No categorical values, including diabetes mellitus and radiation therapy, were significantly associated with radiological non-union. In conclusion, assessing at least two sides (i.e. labial and lingual sides) on CT images is adequate to evaluate bone union in transferred fibula flaps. Careful fixation at the mandibular angle may improve the rate of bone union.